PHYTOCHEMICAL SCREENING OF ETHANOLIC EXTRACT: a Preliminary Test on Five Medicinal Plants on Bangkalan - Laila Khamsatul Muharrami; Fatimatul Munawaroh; Taslim Ersam; Mardi Santoso (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2020)
This study is preliminary research of secondary metabolite potential from medicinal Herb Madura. This study aims to know the medicinal plants used in the medicinal herb Madura and the phytochemical content contained in these medicinal plants. The method used in this study is a survey to know the kinds of medicinal plants used in Madura Herb. Then a phytochemical screening test for the medicinal plant was performed. The phytochemical screening test used are alkaloids, steroids, saponins, and flavonoids. Based on the research, it is found that 66 medicinal plants are widely used for